Peran Komite Sekolah dalam Meningkatkan Mutu Pendidikan - Dra samsidar (Universitas Muhammadiyah Tapanuli Selatan, 2018)
The school committee is an independent body that embraces the participation of the community in order to improve the quality, equity, and efficiency of educational management unified education both in preschool education, school education path, and out-of-school educationThe establishment of a school committee is a body that replaces the existence of the Provision of Education Providers (BP3) through the Decree of the Minister of National Education. 044 / U / 2002. The renaming of BP3 to the school committee is based on the need for full community involvement in improving the quality of education. One of the objectives of establishing a school committee is to increase the responsibility and participation of the community in the implementation of education in educational units.The role of the school committee includes: 1) Considerations. 2) Supporters. 3) Controller. 4) Mediator. The role of the school committee as a supporter includes Resource Management, Facilities and Infrastructure Management, and Budget Management. The role of school committee supporters works with employers and sympathizers. In developing performance with entrepreneurs and responsive to school issues, school committee members are influential people in school as well as with the business world as well as active in the School.Keywords: Role, Committee, Improve quality, Education